Clinico-etiological spectrum of pancytopenia in hospitalized children - Dubey, Shiv Ram Krishna; Patel, Saurabh Kumar; Arya, A. K.; Singh, R. P. (International Journal of Contemporary Pediatrics, 2016)
Background: Pancytopenia is not uncommon in children, having multiple cause varying from transient marrow suppression to leukaemia. There is little discussion regarding pancytopenia in pediatric population especially in South East Asia. Methods: It was a cross-sectional, observational study GSVM Medical College, Kanpur, UP, India from January 2011 to august 2012. All patients admitted between 1-18 years age group presenting with pancytopenia were included for the study. A detailed clinical history and physical examination was done. Bone marrow examination (aspiration) to confirm a particular etiology / or to support a diagnosis. Results: Incidence of Pancytopenia was 2.9% , Most of the patients (30.5%) were in the 13-15 years age group. The common causes were megaloblastic anemia (47%), aplastic anemia (25.8%) and leukemia (17.6%). Common clinical presentation was pallor (81%), fever (68%) and petechial haemorrhages (51%). Conclusions: Pancytopenia is a common medical condition in children, the mean age of presentation being 10.63±4.60 years. There should be high index of suspicion for pancytopenia and early intervention should be done as most the cases are preventable.